Implementasi Algoritma Digital Differential Analyzer dalam Penentuan Rute Pada Peta Topografi berbasis Android - Panji Novantara; Tito Sugiharto; Elpan Januar (Universitas Kuningan, 2021)
The route is direction that must be taken from the starting point to the destination point. Determination of the route is usually done for a reference trip that will be taken include the distance, time or slope of the terrain to be passed. In the implementation, the determination of the route is often used by agencies and organizations operating in the open nature where the activities require special expertise that can process geographic information systems. Although the tools and technology for route determination are sufficient, they are still less effective and efficient because to know the distance, time and slope of a terrain on topographic maps are still using conventional calculations, therefore the application of route determination's topographic maps based android and applying Digital Differential Analizer algorithm. The algorithm can be used as a line maker to display a slope picture of the field being traversed. This application was developed using the Rational Unified Process (RUP) method which has 4 stages: Inception, Elaboration, Contruction, and Transition. This application can be run at least on Android platform version 4.1.Keywords : Geographic Information Systems, Routes, Digital Differential Analizer Algorithm, Android, RUP